TEACHING FIRST AID IN HIGH SCHOOLS: THE IMPACT ON STUDENTS IN THE HEALTH SCIENCES EXTENDED DEGREE PROGRAMME. - Louw, A.; de Villiers, A. (South African Journal of Higher Education, 2015)
Previously, first-year medical and physiotherapy students participating in the extended degree programme (EDP) at Stellenbosch University, South Africa, spent eight weeks shadowing interns at a tertiary hospital during a clinical module. In 2011, student numbers had doubled from the previous year making it impossible to accommodate the entire group in the clinical setting. Consequently, the group was divided into two, allowing one group to participate in a service-learning project (SLP), while the other group spent four weeks in the clinical setting as before. The two groups switched after four weeks. A qualitative approach was used to determine students' perceptions of the SLP. Data was obtained from structured reflective reports about students' experiences of the one-week period during which they taught First Aid to high school learners. Open-ended, written response questionnaires completed by students at the end of the four-week SLP generated further useful data regarding the logistics and administration of the project as a whole. Similar to findings reported in international studies, analysis of qualitative data indicated an increase in student motivation in terms of their studies and vocation; an enhanced sense of civic responsibility and social justice; improved group interaction and personal communication skills; as well as increased compassion and decreased racism. Besides gaining First Aid knowledge and skills, students became increasingly aware of the population they would be serving once they graduated and of their role as professionals within this community. Thus, a service-learning teaching strategy may contribute towards producing service-driven and culturally competent physicians and community leaders.